Description of the 5th instar nymph of Oenopiella punctaria (Stål, 1859) Hemiptera: Heteroptera: Pentatomidae), with new distributional records from Southern Patagonia - Faúndez, Eduardo I.; Carvajal, Máriom A . (Zootaxa, 2016)
The 5th instar nymph of Oenopiella punctaria (Stål, 1859) is described and illustrated for the first time, together with new distributional records from Patagonia. The new records are from Santa Cruz Province (Argentina), and the Magallanes Region (Chile). The latter is the southernmost record for this species and also for the Carpocorini in South America. In light of the new data, the biogeography of Oenopiella is discussed, and it is concluded that an Andean origin may be possible.